Laser mimicking mosquito bites for skin delivery of malaria sporozoite vaccines - Zhou, Chang (J Control Release, 2015)
Immunization with radiation-attenuated sporozoites (RAS) via mosquito bites has been shown to induce sterile immunity against malaria in humans, but this route of vaccination is neither practical nor ethical. The importance of delivering RAS to the liver through circulation in eliciting immunity against this parasite has been recently verified by human studies showing that high-level protection was achieved only by intravenous (IV) administration of RAS, but not by intradermal (ID) or subcutaneous (SC) vaccination. Here, we report in a murine model that ID inoculation of RAS into laser-illuminated skin confers immune protection against malarial infection almost as effectively as IV immunization. Brief illumination of the inoculation site with a low power 532 nm Nd:YAG laser enhanced the permeability of the capillary beneath the skin, owing to hemoglobin-specific absorbance of the light. The increased blood vessel permeability appeared to facilitate an association of RAS with blood vessel walls by an as-yet-unknown mechanism, ultimately promoting a 7-fold increase in RAS entering circulation and reaching the liver over ID administration. Accordingly, ID immunization of RAS at a laser-treated site stimulated much stronger sporozoite-specific antibody and CD8(+)IFN-γ(+) T cell responses than ID vaccination and provided nearly full protection against malarial infection, whereas ID immunization alone was ineffective. This novel, safe, and convenient strategy to augment efficacy of ID sporozoite-based vaccines warrants further investigation in big animals and in humans.